THE ANALYSIS OF FUEL CONSUMPTION STRUCTURE AND CARBON DIOXIDE EMISSIONS BY VIEW OF ENERGY SECURITY IN ENERGETICS OF THE REPUBLIC OF MOLDOVA - Bicova E.V. (Problems of the Regional Energetics, 2008)
In the paper the analysis of fuel consumption block indicators dynamics of energy security indicators system is presented. Calculations results of carbon dioxide emissions in energy security indicators system ecological block are presented as well.